Change in Fluorescence Intensity of Grape Meristem Cells Under Effect of Some Cryoprotective Agents - Stribul, T. F.; Lysak, Yu. S.; Kompaniets, A. M. (Problems of Cryobiology and Cryomedicine, 2010)
The effect of some substances with cryoprotective properties on grape meristem fluorescence and viability was studied. Treated with cryoprotectants meristems were irradiated with laser to excite photoelectron emission and the fluorescence spectra were obtained in 1, 3, 5, 20 and 120 min. It has been established that the effect of cryoprotective agents (CPAs) manifested in the change of fluorescence intensity within the range of the studied wave lengths.